1993
DOI: 10.1161/01.cir.87.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Association of early-onset coronary heart disease in South Asian men with glucose intolerance and hyperinsulinemia.

Abstract: Background. Rates of coronary heart disease are higher in South Asians (Indians, Pakistanis, and Bangladeshis) settled overseas than in other ethnic groups. We tested the hypothesis that this excess risk results from metabolic disturbances associated with insulin resistance.Methods and Results. There were 1,421 South Asian men and 1,515 European men aged 40-69 years in London examined in the Southall Study. Prevalence of ischemic ECG abnormalities was higher in South Asians than in Europeans (17% versus 12%,p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
199
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(214 citation statements)
references
References 40 publications
14
199
0
1
Order By: Relevance
“…27 Population studies show that diabetes, insulin resistance, and related metabolic abnormalities are more common among Indian Asians than European whites, and they may account for up to 70% of major Q-wave ECG abnormalities in Asians. 4,5 In the present study, CRP concentrations were also closely associated with levels of HDL cholesterol, triglycerides, glucose, blood pressure, and a composite insulin resistance score in both racial groups. Similar findings have been reported in North American and European populations, which have additionally shown that CRP concentrations and other inflammatory markers, including white cell count and fibrinogen, are strongly associated with plasma insulin and insulinmediated glucose uptake.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…27 Population studies show that diabetes, insulin resistance, and related metabolic abnormalities are more common among Indian Asians than European whites, and they may account for up to 70% of major Q-wave ECG abnormalities in Asians. 4,5 In the present study, CRP concentrations were also closely associated with levels of HDL cholesterol, triglycerides, glucose, blood pressure, and a composite insulin resistance score in both racial groups. Similar findings have been reported in North American and European populations, which have additionally shown that CRP concentrations and other inflammatory markers, including white cell count and fibrinogen, are strongly associated with plasma insulin and insulinmediated glucose uptake.…”
Section: Discussionsupporting
confidence: 63%
“…1,2 Conventional coronary risk factors, including smoking, hypercholesterolemia, and hypertension, do not explain their increased CHD risk compared with whites. 3,4 Although diabetes and insulin resistance are more prevalent among Indian Asians, 4,5 the precise mechanisms underlying the increased CHD mortality in Indian Asians are not known.…”
mentioning
confidence: 99%
“…A low cut-off age (50 years) to compare prognosis was taken considering the fact that CAD occurs in Indians at a younger age. 7,8 In the GRACE registry, age has been shown to be a statistically significant predictor of events for every 10 years increase in age (OR 1.7/decade). Like in the GRACE registry (OR 1.4 for every 10 mmHg decrease), our study also showed that a lower SBP at admission is significantly associated with more events.…”
Section: Discussionmentioning
confidence: 99%
“…17,71,73 A low prevalence of electrocardiographic Q waves has been observed in two Indian studies which have reported on this finding indicating a lower incidence of arteriosclerosis. 17,73 It is possible that south Asian immigrants to developed countries may have a greater incidence of electrocardiographic changes, due to their increased susceptibility to insulin resistance 8,81 which may be decreased by a diet rich in n-3 fatty acids. 82 Higher body mass index in association with hypertension and a higher fat diet has been observed in Japan.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%